Downward counterfactual analysis of multi-risk cascades - Gargiulo, M. V.; Woo, G.; Battimelli, E.; Amoroso, O.; Napolitano, F.; Russo, R.; Capuano, P. (Frontiers in Earth Science, 2023)
Loss outcomes from geohazards are compounded by an array of human risk factors. The combination of geohazards and human risk factors can generate multi-risk cascades. In the historical record, disasters arising from such multi-risk cascades are comparatively rare. However, far more common are near-misses, where a disaster tipping point to massive destructive energy release and expanding losses was narrowly averted. What happened historically is only one realization of what might have happened. Due to psychological outcome bias, people pay far less attention to near-misses than to actual losses. A downward counterfactual is a psychological term for a thought about the past, where things turned for the worse. Exploration of downward counterfactuals enhances risk awareness and can contribute to risk preparedness. There are no databases of multi-risk cascade near-misses, but insights can be gained from downward counterfactual analysis. Geohazard examples of multi-risk downward counterfactuals are given, including cases of critical infrastructure damage. A downward counterfactual can drive a minor hazard event beyond the disaster tipping point boundary, and turn a disaster into a major catastrophe. To illustrate the latter, a downward counterfactual analysis is presented of the Fukushima nuclear accident of March 11, 2011, which might have crossed the tipping point boundary into a multi-risk cascade catastrophe.